Performance analysis of a wavy fin-and-tube automobile radiator operating on ethylene glycol and water based ternary nanofluids - Ferdinard Dika; Mustafa Dagbasi; Michael Adedeji; Humphrey Adun (Heliyon)
Efficient thermal management is crucial for optimizing the performance and longevity of automotive engines, particularly as environmental regulations become more stringent and consumer demand for fuel efficiency increases. This paper investigates the energy and exergy performance of a wavy fin-and-tube radiator employing novel ternary nanofluids (TNFs) for enhanced automotive cooling. A theoretical comparative analysis was performed on four distinct ethylene glycol-water solution-based TNF configurations. TNF 1 (ZnO-Al2O3-SiO2) is made up of all spherical-shaped nanoparticles; TNF 2 (Al2O3-TiO2-MWCNT) is made up of both spherical and cylindrical nanoparticles; TNF 3 (Fe-TiO2-Graphene) comprises spherical and platelet nanoparticles; and TNF 4 (Al2O3-MWCNT-Graphene) has dissimilar-shaped nanoparticles. The radiator's performance is assessed under simulated idle, city, and highway driving conditions to evaluate its operation in various automotive cooling demands. The results showed that, for most of the radiator operating scenarios and base fluid mixture configurations tested, TNF 1 offers the best performance. Additionally, the change in volume fraction for the EG/W (20:80) base fluid only slightly affects the heat transfer rate and exergy efficiency for TNF 1. However, increasing the volume fraction for the EG/W (50:50) base fluid TNFs has a more significant negative effect. In all radiator operation scenarios, the outlet temperature of the TNFs will decrease relative to the intake temperature. Ultimately, the research found that the TNFs would provide improved performance across all conditions, particularly in city and highway driving scenarios when there is a greater need for cooling.